2022
DOI: 10.3897/neobiota.71.69716
|View full text |Cite
|
Sign up to set email alerts
|

Plant invasions in riparian areas of the Middle Danube Basin in Serbia

Abstract: Riparian areas experience strong invasion pressures worldwide and represent important points of spread for invasive alien plants (IAPs) in the European mainland. The Danube Basin is a well-known point of high plant invasion levels. Given that the middle part of the Danube Basin is critically understudied and the general lack of data for Serbia, the study aimed to provide an insight into the spatial patterns of plant invasions in the riparian areas of Serbia (Middle Danube Basin area). A total of 250 field site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…At higher altitudes, richness values of invasive alien plants decrease quickly. The relationship between increasing altitude and decreasing IAP richness has been often observed (Pyšek et al, 2002;Chytrý et al, 2005Chytrý et al, , 2009An delković et al, 2022), and has been attributed to the generally milder climatic conditions found in low-altitude areas (Chytrý et al, 2005), benefiting IAP that mostly originate from warm areas (Pyšek et al, 2003). On the other hand, the IAP found at higher altitudes are mostly generalists with broad climate tolerances and able to thrive across a wide range of altitudes (Alexander et al, 2011;Essl et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…At higher altitudes, richness values of invasive alien plants decrease quickly. The relationship between increasing altitude and decreasing IAP richness has been often observed (Pyšek et al, 2002;Chytrý et al, 2005Chytrý et al, , 2009An delković et al, 2022), and has been attributed to the generally milder climatic conditions found in low-altitude areas (Chytrý et al, 2005), benefiting IAP that mostly originate from warm areas (Pyšek et al, 2003). On the other hand, the IAP found at higher altitudes are mostly generalists with broad climate tolerances and able to thrive across a wide range of altitudes (Alexander et al, 2011;Essl et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…The presence of P. oleracea was studied at 250 riparian field sites, distributed along 39 rivers and 6 canal sections of the Danube-Tisa-Danube system of canals (Anđelković, 2019;Anđelković et al 2022). The studied rivers were selected with the aim of encompassing nine catchment areas (CAs) in Serbia and thereby ensuring the best geographical coverage of the study area.…”
Section: Field Researchmentioning
confidence: 99%
“…In addition, the riverbank habitat is a fragile ecotone which is vulnerable to invasion [35][36][37][38] and is one of the habitat types with the most significant number of IAS [39,40]. Many IAS drive hydrological changes to form an easier-to-invade riparian environment by altering the nature of habitats [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Many IAS drive hydrological changes to form an easier-to-invade riparian environment by altering the nature of habitats [41][42][43]. They usually start along the watercourses and expand further inland [36]. For example, the invasion rate of Alternanthera philoxeroides is exceptionally high on both sides of river channels.…”
Section: Introductionmentioning
confidence: 99%